Structural characteristics of the tendinous cord-papillary muscle junction in healthy and hypertensive rats - Domingo Francia-Farje, Luis Alberto; Diniz Almeida-Francia, Camila Contin [UNESP]; Michelin Matheus, Selma Maria [UNESP]; Torrejais, Marcia Miranda; Soares, Jair de Campos [UNESP] (Pergamon-Elsevier B.V. Ltd, 2009)
Although the myotendinous junction (MTJ) of skeletal striated muscle is well known, more detailed studies regarding the structure of the cardiac MTJ are scarce. The objective of the present study was to investigate the morphological characteristics of the MTJ in hearts of healthy and hypertensive (SHR) female rats using histological, ultrastructural and three-dimensional (SEM) methods, as well as to evaluate the expression of vinculin by immunofluorescence. In the two groups, light microscopy showed branching tendinous cords and collagen bundles penetrating the apex of the finger-like projections of the papillary muscle. SEM analysis revealed an enlarged apex of the papillary muscle in SHR which was not observed in healthy animals. The loss of force transmission appears to be compensated by the amplified connection between the papillary muscle and valvular collagen. A large number of intercalated disks close to the fiber apex, small amounts of an amorphous intercellular substance and numerous vesicles were observed in SHR. In these animals, the expression of vinculin was more marked showing a regular distribution and a pattern of transverse striations along the sarcolemma. The presence of this protein in transverse bands suggests that vinculin surrounds myofibrils in the region of the Z band. Vinculin staining was also more marked in the region of the tendinous cord-papillary muscle junctions of SHR compared to control animals. Vinculin was quantified by electrophoresis and higher amounts of this protein were observed in SHR compared to control animals. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Heart; Hypertensive rats; Myotendinous junction; Tendinous cord; Ultrastructure; Vinculin